Ecogeographical Amplitude and Habitat of Two Species of the Genus- Terminalia (Combretaceae) In the Central Niger Delta Areas in Rivers State - NL Edwin-Wosu; T Omara-Achong; BL Nyannanyo (Journal of Applied Sciences and Environmental Management)
A systematic study involving phytogeography was carried out on two species of the genus-Terminalia in the Central Niger Delta Areas in River State. This research was aimed at establishing their biodynamic distribution and habitat in the study areas using the simple random sampling method based on standard procedure for ecological assessment. Result shows that both species are successfully adapted to the area as mesophytes but are distinct in all aspect, thus have marked preference for and /or by displaying restricted occurrence in certain ecological habitat. Terminalia ivorensis does occur wildly and in abundant in the forest than T. catappa, which is frequently cultivated around homes and residential areas, though occurred more in fresh water ecozone. Both species are deciduous with annual foliar senescence. Both species were also observed to be utilized for different purposes such as environmental conservation, beautification, parks and habitat and as shade creating plants and domestic source of fuel in the Central Niger Delta